Integrating Indigenous Values into Sustainable Ecological Cultural Learning: A Model for Elementary Education - Istiqfaroh, Nurul; Hendratno; Supeno (CV. Kurnia Grup, 2025)
This study aimed to develop and validate a Sustainable Ecological Cultural Learning (SECL) model integrated with indigenous values for elementary education. The model was designed to address the limited integration of ecological sustainability and cultural literacy in elementary school learning while supporting culturally responsive and sustainability-oriented education. This study employed a research and development approach using the ADDIE framework, focusing on the analysis, design, and development stages, with evaluation limited to expert-based validity testing. The SECL model was validated by experts in elementary education, environmental education, and cultural studies using a structured validation instrument with a four-point Likert scale. The validation results indicate that the SECL model achieved an overall mean validity score of 3.53 out of 4.00, categorized as very valid. High validity scores were obtained across key aspects, including integration of indigenous values (M = 3.70), relevance to sustainable education principles (M = 3.60), and alignment with elementary student characteristics (M = 3.55). These findings demonstrate that the SECL model is conceptually sound, feasible, and appropriate for elementary education contexts. The validated model provides a solid foundation for further classroom implementation and effectiveness testing in future studies.